2008
DOI: 10.1038/onc.2008.160
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-inducible factor-2 regulates vascular tumorigenesis in mice

Abstract: The von Hippel-Lindau tumor suppressor pVHL regulates the stability of hypoxia-inducible factors (HIF)-1 and -2, oxygen-sensitive basic helix-loop-helix transcription factors, which mediate the hypoxic induction of angiogenic growth factors such as vascular endothelial growth factor. Loss of pVHL function results in constitutive activation of HIF-1 and HIF-2 and is associated with the development of highly vascularized tumors in multiple organs. We have used a conditional gene-targeting approach to investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
102
2
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(109 citation statements)
references
References 20 publications
3
102
2
2
Order By: Relevance
“…Previous studies have consistently shown that developmental abnormalities caused by Vhl deficiency are partially reversible in double knockout animals with HIF deletion. 28,45,46 Nevertheless, pVHL exerts important HIFindependent effects on, for example, matrix metabolism and cytoskeletal function. 10,47 Our study also sheds some light on the role of the functional consequences of disturbed development of renin-producing cells, which were overall surprisingly minor.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have consistently shown that developmental abnormalities caused by Vhl deficiency are partially reversible in double knockout animals with HIF deletion. 28,45,46 Nevertheless, pVHL exerts important HIFindependent effects on, for example, matrix metabolism and cytoskeletal function. 10,47 Our study also sheds some light on the role of the functional consequences of disturbed development of renin-producing cells, which were overall surprisingly minor.…”
Section: Discussionmentioning
confidence: 99%
“…The hypothesis is supported by the observation that knockdown of HIF-2α in neuroblastoma and glioma stem/tumor initiating cells results in poorly vascularized tumors. Moreover, vascularization is affected in mice with eliminated Hif2a (Peng et al 2000;Rankin et al 2008) and overexpression of Hif2a in embryoid bodies results in early and extensive formation of a vascular network (Covello et al 2006). The underlying molecular mechanisms behind the perivascular localization of neural tumor stem cells is presently not understood and is a topic of future investigations.…”
Section: Hifs and Vascularizationmentioning
confidence: 99%
“…As the cell type directly in contact with the blood, endothelial cells must adapt to changing conditions within the blood vessels and synthesize regulators of leukocyte and vascular smooth muscle cell behavior. Medical conditions, such as atherosclerosis, varicose veins, pulmonary hypertension, and tumor angiogenesis, may induce vascular hypoxia (Eyries et al, 2008;Han et al, 2008;Kubo et al, 2008;Osada-Oka et al, 2008a;Rankin et al, 2008), and the molecular aspects of hypoxia have been studied in order to explain the pathology underlying these diseases; however, many questions remain.…”
Section: Introductionmentioning
confidence: 99%